A Rare De Novo Balanced X; 1 Translocation in an Indian Female with Primary Amenorrhea - A Venkateshwari; A Srilekha; K Veena; M Sujatha; A Jyothy (JRI, 2015)
Background: Translocations involving X chromosome and an autosome are rather rare due to associated infertility in men and subfertility in women. X chromosome translocations are frequently associated with primary or secondary amenorrhea. In this report, a case of primary amenorrhea with a de novo balanced reciprocal translocation was presented between chromosomes X and 1. Case Presentation: A 24 year-old proposita with the complaint of primary amenorrhea was found to have hypoplastic uterus and streak gonads with a normal hormonal profile. Chromosomal analysis of the proband revealed a de novo translocation of 46, X, t(X; 1) (q21; p32) chromosomal constitution. Parental karyotypes of the proband showed normal karyotype. Conclusion: The observed translocation between chromosome X and 1 in the patient suggest either the disruption of a critical gene expression due to position effect or deletion of one or more essential genes in the disrupted long arm of the affected X chromosome. To the best of our knowledge, this is the first report from our ethnic group.